2016
DOI: 10.1177/1099800416631819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low Back Pain Recovery and Persistence

Abstract: Background Persistent low back pain is a significant problem worldwide. Early identification and treatment of individuals at high risk for persistent low back pain have been suggested as strategies to decrease the rate of disability associated with this condition. Purpose To examine and compare demographic, pain-related, psychological, and somatosensory characteristics in a cohort of participants with acute low back pain who later went on to experience persistent low back pain or whose pain resolved within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Recruitment took place at primary healthcare clinics through advertisements. More detail is available in Starkweather, Lyon, et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruitment took place at primary healthcare clinics through advertisements. More detail is available in Starkweather, Lyon, et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In a cohort of patients with acute low back pain, a standardized QST protocol was used to measure the threshold and tolerance of noxious mechanical and thermal stimuli at the painful site of the lower back and a remote site (dominant forearm) (Starkweather, Lyon, et al, 2016). Some of the participants manifested signs of peripheral and central sensitization to mechanical and thermal stimuli as evidenced by reduced thresholds at both the painful region of the low back and the remote site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Starkweather and colleagues simultaneously examined differences in peripheral and central sensitivity and expression levels of pain sensitivity genes at the onset of low back pain and over time in patients with an acute episode that either resolved or became chronic (Starkweather, Lyon, et al, 2016). Participants enrolled in the study during an acute phase of low back pain and categorized as either “recovered” if their pain resolved in the first six weeks after onset or as “persistent” if their pain continued for six months.…”
Section: Nursing Science Exemplar: Genomicsmentioning
confidence: 99%
“…The team’s initial goal was to identify differential expression pain genes at the onset of acute low back pain. They found that participants with acute low back pain had significantly increased expression of prepro-nociceptin ( PNOC ), the precursor of nociceptin, chemokine (C-C motif) ligand 2 ( CCL2 ), and cannabinoid type-2 (CB2) receptor ( CNR2 ) compared to the healthy no-pain control group (Starkweather, Ramesh, et al, 2016). In addition, dysregulated expression of multiple genes involved in pain processing were identified at the onset of acute low back pain, including GCH1, CSF1, TRPV1, CALCA, PTGES, GDNF , and KCNQ2 .…”
Section: Nursing Science Exemplar: Genomicsmentioning
confidence: 99%